SCK-CEN Contribution to the IAEA Round Robin Exercise on WWER-440 RPV Weld Material: Irradiation, Annealing, and Re-Embrittlement - Lucon, E.; Walle, E. van; Scibetta, M.; Chaouadi, R.; Weber, M. (Проблемы прочности, 2004)
Mechanical properties of WWER-440 RPV weld joints have been studied with account of different states of the material: baseline (unirradiated), irradiated up to the average fast neutron fluence of 6.5*10^19 n/cm^2, irradiated and eventually annealed, re-irradiated with the accumulated fast neutron fleunce 1.3*10^20 n/cm^2. For each state of the material, tensile, impact fracture, and fracture toughness tests were performed with the use of Charpy (standard, reconstituted, and pre-cracked) specimens. Исследованы механические свойства материалов сварных соединений корпусов реакторов ВВЭР-440 с учетом различных состояний: исходного (неохрупченного), после радиационного охрупчивания со средней плотностью потока нейтронов до 6,5*10^19 нейтр/см^2, охрупченного с последующим отжигом, повторно охрупченного с флюэнсом частиц 1,3*10^20 нейтр/см^2. Для каждого состояния материала проведены испытания на растяжение, ударное разрушение и трещиностойкость с использованием образцов Шарпи (стандартные, восстановленные, с предварительно нанесенной трещиной). Досліджуються механічні характеристики зварних з ’єднань корпусів реакторів BBEP-440 з урахуванням різного стану: початкового (неокрихчувано- го), після радіаційного окрихчування з середньою густиною потоку нейтронів до 6,5*10^19 нейтр/см^2, окрихчуваного з наступним відпалом, повторно окрихчуваного з флюенсом частинок 1,3*10^20 нейтр/см^2. Для кожного стану матеріалу проведено дослідження на розтяг, ударне руйнування та тріщиностійкість із використанням зразків Шарпі (стандартні, відновлені та з попередньо нанесеною тріщиною).